Estradiol inhibits NLRP3 inflammasome in fibroblast‐like synoviocytes activated by lipopolysaccharide and adenosine triphosphate. (3rd November 2017) - Shi, Jianfeng; Zhao, Weibo; Ying, Haijian; Zhang, Ying; Du, Juping; Chen, Shuaishuai; Li, Jun; Shen, Bo
Abstract: Objective: Nucleotide binding domain and leucine‐rich repeat pyrin 3 domain (NLRP3) inflammasome is known for activating pro‐inflammatory cytokines in knee osteoarthritis (OA). This study was performed to identify whether NLRP3 inflammasome can be triggered by lipopolysaccharides (LPS) and adenosine triphos adenine (ATP), which are positively related with knee OA severity in joint‐spaces, in human fibroblast‐like synoviocytes (FLS), and to identify whether estrogen would inhibit the activation of NLRP3 inflammasome. Methods: In the present study, human FLS were isolated from the knee OA in patients during arthroplasty, and were treated with LPS and ATP in the presence or absence of estradiol (E2). The messenger RNA (mRNA) and protein levels of NLRP3 components were analyzed by real‐time polymerase chain reaction and western blotting, respectively. Enzyme‐linked immunosorbent assay (ELISA) was used to examine interleukin (IL)‐1β and IL‐18 content in the supernatant. Estrogen receptor α inhibitor MPP and β inhibitor PHTPP were used to explore how E2 works. Results: Our results demonstrated that treatment with LPS and ATP increased significantly both in mRNA and protein levels of all the NLRP3 inflammasome components, and triggered the NLRP3 inflammasome, followed by upregulated IL‐1β and IL‐18 in the cell supernatant. E2 appeared to inhibit the activation of NLRP3 inflammasome by diminishing mRNA and protein levels of NLRP3 through estrogen receptor β, and decreased the expression of IL‐1β and IL‐18 as well. Conclusion: These results suggested the increased LPS and ATP in joint‐space may promote knee OA by NLRP3 inflammasome and E2 may exert a protective effect by inhibiting the activation of NLRP3 inflammasome in FLS.